Electrolyte Disturbance in Diarrheal Children Infected with Giardia lamblia in Tikrit City - Khalaf , Qutaiba Ali Saleh; Daham, Shahad Saad; Athab, Elham Khalef (American Journal of Biology and Natural Sciences, 2026)
Background: Giardia intestinalis, or G. lamblia, is a flagellated protozoan parasite that induces diarrhea. Electrolyte imbalances frequently occur in people with diarrhea and can lead to considerable morbidity. Objective: To ascertain the incidence and patterns of electrolyte abnormalities, specifically hyponatremia, hypokalemia, and hypochloremia. Materials and methods: One hundred eighty stool samples were obtained from children of both genders and various age groups, ranging from 2 to 12 years, residing in Tikrit city and adjacent villages, who attended an outpatient clinic between September and December 2025. Result: The samples were examined directly using the Direct Wet Mount technique, and the results showed that 62 samples (34.4%) were positive for Giardia lamblia. The results of infection with the parasite were higher in males than in females, reaching about 45.5%, while it reached 26.2%in females. A significant decrease the mean and SD of sodium, and chloride, diarrheal patient with G. lamblia, that were (135±0.51, 96.2 ±0.78) in compared with control at p-value <0.05. While non -significant differences in potassium level that was (4.71 ±0.06) in G. lamblia as compared with control, at p-value >0.05. Conclusion: This epidemiological study documents the incidence of the intestinal parasite G. lamblia among children in Tikrit, Iraq. The current study concluded an increased prevalence of G. lamblia in children with diarrhea. Furthermore, the prevalence incidence is higher in males than in females. Moreover, the electrolyte imbalance in diarrheal toddlers infected with G. lamblia resulted in decreased salt and chloride levels.